1997
DOI: 10.1097/00004691-199701000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Filtering of Multichannel Electroencephalographic Recordings Through Principal Component Analysis by Singular Value Decomposition

Abstract: Principal component analysis (PCA) by singular value decomposition (SVD) may be used to analyze an epoch of a multichannel electroencephalogram (EEG) into multiple linearly independent (temporally and spatially noncorrelated) components, or features; the original epoch of the EEG may be reconstructed as a linear combination of the components. The result of SVD includes the components, expressible as time series waveforms, and the factors that determine how much each component waveform contributes to each EEG c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
160
0
4

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(166 citation statements)
references
References 11 publications
2
160
0
4
Order By: Relevance
“…In cases where bad channels were detected they were replaced with the average of the nearest surrounding electrodes (3-4 electrodes). Next, ocular artefact was removed from all continuous EEG recordings using a Spatial Singular Value Decomposition (SVD) technique [37,38]. In this technique the EOG calibration recording was first epoched into Horizontal, Vertical and Eye blink events, then a Spatial Singular Value Decomposition (SVD) transform was applied to the epochs in order to derive two independent components accounting for vertical/horizontal eye movements and blinks.…”
Section: Eeg Recording and Data Reductionmentioning
confidence: 99%
“…In cases where bad channels were detected they were replaced with the average of the nearest surrounding electrodes (3-4 electrodes). Next, ocular artefact was removed from all continuous EEG recordings using a Spatial Singular Value Decomposition (SVD) technique [37,38]. In this technique the EOG calibration recording was first epoched into Horizontal, Vertical and Eye blink events, then a Spatial Singular Value Decomposition (SVD) transform was applied to the epochs in order to derive two independent components accounting for vertical/horizontal eye movements and blinks.…”
Section: Eeg Recording and Data Reductionmentioning
confidence: 99%
“…Principal component analysis (PCA) was applied to the EEG signals and only components with a signal-to-noise ratio greater than 1.0 were retained (Lagerlund et al, 1997). A spherical volume conductor head model was adopted, which consisted of three compartments representing the brain, skull, and scalp (Niedermeyer and da Silva, 1999).…”
Section: Eeg Source Reconstructionmentioning
confidence: 99%
“…However, PCA cannot completely separate eye artifacts from brain signals, especially when they have comparable amplitudes (Lagerlund et al, 1997;Jung et al, 1998bJung et al, , 2000. By combining PCA, multiple source models for EOG and EEG, and an artifact-aligned averaging method (Lins et al, 1993), Berg and Scherg (1994) demonstrated a more effective PCA-based approach to correct eye artifacts.…”
Section: Introductionmentioning
confidence: 99%